The Impact of Sleep Quality on Subjective Wellbeing Among Older Adults With Multimorbidity: A Moderated Mediation Model - Zhang, Chichen; Dong, Fang; Zheng, Xiao; Xue, Yaqing; Xiao, Shujuan; Shi, Lei; Xue, Benli; Zhang, Jiachi; Ou, Weiyan (Frontiers in Psychology, 2022)
Background: Studies have found that poor sleep quality is negatively associated with subjective well-being in older adults, but the mechanisms underlying are unclear. In this study, we aimed to examine the mediating role of negative emotions and the moderating role of perceived social support in the relationship between sleep quality and subjective well-being in older adults with multimorbidity. Methods: A multi-stage random sampling method was used to select a sample of 3266 older adults aged 60 years and older. The Memorial University of Newfoundland Scale of Happiness, Pittsburgh Sleep Quality Index, Depression Anxiety Stress Scales-21, Perceived Social Support Scale were used to assess subjective well-being, sleep quality, negative emotional states, and perceived social support, respectively. The moderated mediation models were examined using SPSS PROCESS Version 3.3 software. Results: Sleep quality had a significant direct effect on subjective well-being in older adults (β = −0.997, t = −11.783, P <0.001). Negative emotions partially mediated the effect of sleep quality on subjective well-being (ab=-0.608, 95%CI: -0.728, -0.497). The indirect effect was moderated by perceived social support (β=-0.038, 95%CI:-0.062, -0.014, P<0.001; β=-0.002, 95%CI:-0.004, -0.01, P=0.008). Conclusions: Negative emotions increased the negative association between sleep quality and the subjective well-being of older adults with multimorbidity, and perceived social support played a moderating role. Psychological and behavioral interventions should be implemented as early as possible to promote mental health and enhance social support level of older adults with multimorbidity, and ultimately improve the subjective well-being of older adults.